Hepatotoxicity - Streba, Costin-Teodor; Rogoveanu, Ion; Constantin Vere, Cristin (IntechOpen, 2022)
This book discusses the various therapeutic agents and pathologies that can have a negative impact on liver function. The profound changes such agents may exert on the liver, an essential organ, can severely alter a patient's metabolism, negatively impacting the course of a disease and thus significantly shortening life expectancy and negatively affecting outcomes. This book provides a comprehensive overview of these selected issues with chapters on epidemiology, pathogenesis, clinical manifestations, diagnostic methods, and treatment options in the context of hepatotoxicity.